Antimicrobial Potential of Streptomyces ansochromogenes (PB3) Isolated From a Plant Native to the Amazon Against Pseudomonas aeruginosa - Amorim, Erika Alves da Fonseca; Castro, Erima Joussiely Mendonça; Souza, Silva Viviane da; Alves, Mateus Silva; Dias, Léo Ruben Lopes; Melo, Maycon Henrique Franzoi; da Silva, Ilana Mirian Almeida; Villis, Paulo Cesar Mendes; Bonfim, Maria Rosa Quaresma; Falcai, Angela; Silva, Maria Raimunda Chagas; Monteiro-Neto, Valério; et al. (Frontiers in Microbiology, 2020)
The objective of this study was to evaluate the antibacterial action of filamentous bacteria isolated from the Byrsonima crassifolia leaf. An endophytic bacterium has been identified by classical and molecular techniques as Streptomyces ansochromogene. Screening for antibacterial action against pathogens with medical relevance (Klebsiella pneumoniae ATCC 700603, Pseudomonas aeruginosa ATCC 15692, Staphylococcus aureus ATCC 6538, Corynebacterium diphtheriae ATCC 27012, Mycobacterium abscessus, Cryptococcus gattii ATCC 24065, and Cryptococcus neoformans ATCC 24067) demonstrated activity against the bacterium P. aeruginosa ATCC 0030 with inhibition diameter zones (IDZ) of 17.6 ± 0.25 mm in the preliminary screening in solid medium. After fermentation in liquid medium, an IDZ of 19.6 ± 0.46 mm and a minimum inhibitory concentration (MIC) of 0.5 mg/mL were detected. The antibiofilm action was observed with 100% inhibition of biofilm formation at a concentration of 0.250 mg/mL. When the infection curve was prepared, it was observed that the metabolite was effective in protecting the larvae of Tenebrio molitor. The metabolite does not show toxicity for eukaryotic cells. The leishmanicidal activity demonstrated that the metabolite presented a dose-dependent effect on the promastigotes forms of Leishmania amazonensis growth and the estimated IC50/72 h was 71.65 ± 7.4 μg/mL. Therefore, it can be concluded that the metabolite produced by the endophytic bacterium Streptomyces sp. is promising for future use as an alternative strategy against bacterial resistance.